Biosynthetic potential of Inonotus obliquus in symbiosis with bacterial cellulose: Optimisation and prospects - Parshenkov Mikhail Alekseevich; Skovorodko Polina Petrovna; Petrusevich Danila Alexandrovich; Makaeva Shagun Narimanovna; Osipova Svetlana Guramovna; Ibragimova Gumru; Istyagina Alexandra Olegovna; Balaeva Kristina Anatolievna (Scripta Medica)
Background/Aim: Inonotus obliquus, commonly known as the Chaga mushroom, is an extensively studied source of bioactive compounds, including polyphenols, triterpenoids and polysaccharides. These metabolites exhibit potent antioxidant, anti-inflammatory and immunomodulatory properties, underscoring I obliquus as a valuable resource for advanced biopharmaceuticals and functional therapeutics. Yet, achieving consistent and high-yield biosynthesis of these compounds remains challenging. Aim of this study was to develop a biotechnological approach leveraging co-cultivation with the bacterial cellulose producer Gluconacetobacter hansenii to improve both the yield and stability of these bioactive metabolites. Methods: I obliquus was cultivated on solid and liquid-phase substrates, with and without G hansenii co-cultivation. Biomass yield, morphological changes and growth dynamics were assessed. Total phenolic content and antioxidant activity were quantified using the Folin-Ciocalteu method and DPPH/ABTS assays. Anti-inflammatory properties were evaluated by measuring IL-6, TNF-a and IL-1b levels in LPS-stimulated THP-1 macrophages via ELISA. Results: Co-cultivation with G hansenii resulted in a 1.8-fold increase in fungal biomass yield (30.6 g/L on HS medium) and a 1.3-fold enhancement in phenolic content (85.4 mg GAE/g) compared to monoculture. Extracts from HS medium exhibited the highest antioxidant activity (IC50 = 43.2 µg/mL in DPPH and 29.8 µg/mL in ABTS assays) and significantly reduced pro-inflammatory cytokine levels (IL-6 by 47.5 %, TNF-a by 42.8 % and IL-1b by 39.6 %) in LPS-stimulated macrophages. Morphological analysis revealed a denser, more organised fungal network under co-cultivation, suggesting improved metabolic efficiency and bioactive compound synthesis. Conclusion: Co-cultivation with G hansenii provides a scalable and efficient strategy to enhance the bioactive potential of I obliquus. This approach significantly improves metabolite yield, antioxidant capacity and anti-inflammatory activity, opening new avenues for the development of standardised therapeutic formulations targeting oxidative stress and immune modulation.